Waste valorization: Transforming the fishbone biowaste into biochar as an efficient persulfate catalyst for degradation of organic pollutant. (1st April 2021) - Ren, Xiaoya; Wang, Jingjing; Yu, Jiangfang; Song, Biao; Feng, Haopeng; Shen, Maocai; Zhang, Hao; Zou, Jiajing; Zeng, Guangming; Tang, Lin; Wang, Jiajia
Abstract: Fishbone is a major by-product of fishing processing and how to deal with the increasingly generated fishbone has been a big challenge. In an effort to convert the low-value waste into valuable material, this research explores the valorization of fishbone biowaste, which can be transformed into biochar as a persulfate activator for phenol removal. The fishbone derived biochar (FBBC) was prepared by one-step pyrolysis without additional template. The catalytic efficiency of FBBC increases with pyrolysis temperature, with FBBC-800 (pyrolyzed at 800 °C) exhibiting the best performance of 100% phenol (20 mg/L) removal within 60 min at the catalyst dosage of 0.1 g/L, which is comparable to other recently reported carbon-based catalysts but with the advantage of easy preparation, low cost and wastes valorization. The high efficacy of FBBC-800 is related to its large surface area (758.44 m 2 /g), carbonyl group and defective structure. In the FBBC-800/peroxydisulfate/phenol system, both radical and non-radical pathways are involved, among which hydroxyl radical is more important in radical pathway while singlet oxygen dominates in non-radical pathway. Electron transfer plays a key role in this process through electron capture experiment and electrochemical characterization. This study proposes a new strategy for the valorization of fishbone, and provides the guidance for the structure design of carbon-based catalyst for persulfate activation. Graphical abstract: Image 1 Highlights: A new strategy for fishbone valorization was developed. The fishbone derived biochar is cost effective and easy to prepare. High surface area, carbonyl group and defective structure contribute to the catalytic activity. SO4 · −, · OH, O2 · − and 1 O2 were identified in the catalytic reaction. Electron transfer mechanism for pollutant degradation was proposed.